Analysis of Perceptions of UIN Sunan Ampel Surabaya Students Regarding the Existence of Sharia Banking - Isnaini Maulidatu Nisa’; Muhammad Yazid (al-Afkar, Journal For Islamic Studies, 2024)
Indonesia operates a dual banking system, namely a conventional banking system using an interest rate system and Islamic banking with a profit-sharing system. The growth of Islamic banks has not been able to keep up with conventional banks. This can be seen from the low market share of Islamic finance. There needs to be a strategy and model to increase public understanding of Islamic banks. The "Blueprint for Islamic Banking Development in Indonesia" includes a series of strategic initiatives with clear priorities to address key challenges and achieve goals in the next 10 years, including the achievement of a sizable market share for Islamic banking by deepening the role of Islamic banking in national, regional, and international financial activities, in addition to the vision, mission, and objectives of Islamic banking development. The study aims to determine the development strategy and increase understanding of Islamic banks and describe public perceptions of the existence of Islamic banks. The data collection method is done by drawing samples from the population: namely students and female students of UIN Sunan Ampel Surabaya. The technique of collecting data through questionnaires, while analyzing the data by analyzing the validity, reliability and finding the percentage of respondents. The results showed that the data we studied showed validity because we used validity and reliability tests. There is still indecision/neutral attitude of the community towards the understanding of usury.